KUALITAS PRODUK, HARGA DAN KUALITAS PELAYANAN PADA KEPUASAN KONSUMEN SALON FIFIT MARISSA HIANG: Indra Budaya - Indra, Indra budaya (LPPM STIA Nusantara Sakti, 2024)
This study aims to find out: 1. To determine the effect of product quality on consumer satisfaction of Fifit Marissa Hiang salon partially and how much influence it has. 2. To find out the effect of price on consumer satisfaction of Fifit Marissa Hiang salon partially and how much it influences. 3. To find out the effect of service quality on customer satisfaction of Fifit Marissa Hiang salon partially and how much influence it has. 4. To determine the effect of product quality, price and service quality on consumer satisfaction of Fifit Marissa Hiang salon simultaneously and how much influence. The research methodology used is with qualitative descriptive and quantitative descriptive approaches. The results of the study are; 1. Product quality does not affect customer satisfaction of Fifit Marissa Hiang salon as evidenced by the tcount value is smaller than the ttabel value and the magnitude of the effect is only 4.63%. 2. Price has no effect on customer satisfaction of Fifit Marissa Hiang salon as evidenced by the -tcount value greater than the -ttabel value and the magnitude of the influence is -1.37%. 3. The quality of service affects the customer satisfaction of Fifit Marissa Hiang salon as evidenced by the calculated value greater than the ttabel value and the magnitude of the effect is 14.70%. 4. Partially, product quality, price and service quality affect customer satisfaction of Fifit Marissa Hiang salon, as evidenced by the Fcalculate value greater than the Ftabel value and the magnitude of the effect is 18%